Rancang Bangun Aplikasi Logbook Maintenance Berbasis Web Pada BBMKG Wilayah I Medan - Samsudin Samsudin; Ismi Hamidah Rasyad; Faiz Wahyu Perdana Rangkuti (G-Tech: Jurnal Teknologi Terapan, 2024)
The use of website technology is an effective solution for BBMKG Region I Medan in overcoming obstacles to managing equipment maintenance which still uses manual logbooks. By building a website-based maintenance logbook information system using the waterfall method from SDLC, technicians can manage equipment, accounts, crew and maintenance data efficiently. The system analysis and modeling stages using UML are the basis for designing the implemented system. By using the programming languages PHP, HTML, CSS, JavaScript, and the MySql database server, this system has succeeded in increasing technician effectiveness, producing accurate information, and minimizing data errors. It is hoped that this system will be an effective solution in managing maintenance of BBMKG Region I Medan equipment, supporting digital transformation which is currently developing rapidly.